Optimal Implementation of Antimicrobial Stewardship in General Practice: protocol for a feasibility study and evaluation of a digital AMS Toolbox - Colin H. Cortie; Mary A. Burns; Margaret Jordan; Judy Mullan; Grant M. Russell; Nicholas Zwar; Danielle Mazza; Jan Radford; Gregory M. Peterson; Indra Gajanayake; Simon Eckermann; Stephen Barnett; et al. (Pilot and Feasibility Studies)
Abstract Background Antimicrobial resistance is a worldwide problem caused by the inappropriate use of antibiotics. In Australia, antibiotics are frequently prescribed in general practice (primary care) settings for acute respiratory infections (ARIs) despite these infections most commonly being caused by viruses. The Optimal Implementation of Antimicrobial Stewardship in General Practice (OptimasGP) study aims to provide implementation support for effective antimicrobial stewardship (AMS) interventions for ARIs. The current study will examine if a redesigned workflow, and an AMS Toolbox containing AMS resources, is an acceptable way to access AMS interventions and clinical data collected in general practice settings. Methods A mixed-methods approach will be applied using a single-arm, pragmatic exploratory study. Data will be collected for a period of 3 months. Data collection from general practice settings in New South Wales, Australia, will involve the participation of 4 to 6 practices, 12 general practitioners (GPs), and 6 to 8 practice staff. We also aim to recruit 50–100 patients to complete surveys and 12 patients to participate in focus group discussions. Participating GPs and practice staff will be provided with an online AMS Toolbox to facilitate access to AMS resources. Two hours of online training and a reminder card will also be provided. The AMS Toolbox will contain AMS resources for shared decision-making, clinical decision support (including point-of-care testing), and delayed antibiotic prescribing in patients with ARIs. The primary outcome of the study will be the acceptability of the AMS Toolbox to GPs, practice staff, and patients. Secondary outcomes will include recruitment and completion rates, qualitative findings from the focus group discussions, resource use and antibiotic prescription rates, patient-reported outcome measures (PROMs), and patient-reported experience measures (PREMS). Discussion AMS interventions are needed to help reduce inappropriate antibiotic prescribing for ARIs in general practice settings. The findings of this study will inform a hybrid type 3 implementation trial. Trial registration Registered prospectively with the Australian and New Zealand Clinical Trial Registry (ACTRN12624001011572) on 20 August 2024.